If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 8 = 2t + 6 Reorder the terms: 8 + 4t = 2t + 6 Reorder the terms: 8 + 4t = 6 + 2t Solving 8 + 4t = 6 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 8 + 4t + -2t = 6 + 2t + -2t Combine like terms: 4t + -2t = 2t 8 + 2t = 6 + 2t + -2t Combine like terms: 2t + -2t = 0 8 + 2t = 6 + 0 8 + 2t = 6 Add '-8' to each side of the equation. 8 + -8 + 2t = 6 + -8 Combine like terms: 8 + -8 = 0 0 + 2t = 6 + -8 2t = 6 + -8 Combine like terms: 6 + -8 = -2 2t = -2 Divide each side by '2'. t = -1 Simplifying t = -1
| 2x=31/4 | | 4x=y+1 | | -1.8(2.5x+1.3)=15.66 | | -5[18-7]=9 | | (w^2-630w+3125)=0 | | 0,55x=0,1(2,5x+0,2) | | 2(5y+3)=64 | | X-0.25X=238.93 | | Ln(5x)=4 | | p^2-11p+19=-5 | | 7x+7=3z-7 | | -3b(0.5)=(0.5) | | 3z-7=7x+7 | | -(3x+5)(5x+2)= | | 7x+7+3z-7=90 | | 5x+2a=66 | | 35x+(-185)=750-50x | | 6a^2+16a-70=0 | | q+404=882 | | 4.04x+8.08=16.16 | | 5(x+8)-3(x+8)=4(x+8)-3x | | 5*a=60 | | 3x=196 | | -4+c=24 | | 0.33+1.66=9.99 | | (3x-1)/2=2/3 | | -11+2x=4x+17 | | (7/10y^2)(-2y^3)(3y^2) | | -3+6y=6y | | -192+2x=11x+78 | | -15a^2+34a-15=0 | | 3d=6+3d |